Peranan Risk Based Audit Pada Bagian Kredit Dalam Mengevaluasi Proses Kredit - Gusti Ayu Kade Ratih; Putu Cita Ayu (Hita Akuntansi dan Keuangan, 2023)
This study aims to determine how the application of Risk-Based Audit on the credit department of PT. BPR Bank Kertiawan in order to improve the efficiency and effectiveness of the entity's internal audit. The results showed that the key business process credit at PT. BPR Bank Kertiawan which has a high risk is the Credit Analysis section which affects the credit take over process and the making of a Credit Agreement and its supporting documents so that for further examination, SKAI will focus on the Credit Analysis section which has a high inherent risk